Die nächste große Erzählung - oder warum Hegel immer noch unterschätzt wird - Gessmann, Martin (Philosophische Rundschau, 2024)
Since the end of Marxism, philosophy has also struggled with Hegel, both in political as well as in academic discourse. It almost seems as if the more precisely and thoroughly the texts are studied, the less relevant they become. This is astonishing in view of the new developments of the present, or as Hegel would say, the state of our Zeitgeist. On the world stage, we are still in the midst of the aftermath of the revolutions of 1989; socially, we are already looking ahead to a 4th industrial revolution, with all the consequences that can already be foreseen from digitalization and the use of artificial intelligence. A historical parallel to Hegel comes to mind, which must be taken seriously if philosophy is still to be there to capture its "time in thought". Popular Hegelian literature in particular appears to have a duty to reflect on our new situation in this way. What new insights emerge from their attempts and how philosophy can once again create a sovereign overview will be clarified in the following review essay. In the end, there is a decisive plea to give the grand narrative a chance again within philosophy.Moritz Rudolf, Der Weltgeist als Lachs. Berlin: Matthes & Seitz 2021. 126 S. Hans Ulrich Gumbrecht, Weltgeist im Silicon Valley. Leben und Denken im Zukunftsmodus. Basel, NZZ Libro 2018. 238 S. - Richard Bourke, Hegel's World Revolutions. Princeton & Oxford: Princeton University Press 2023. XVI, 321 S. - Klaus Vieweg, Hegel. Der Philosoph der Freiheit. Biographie. München: C.H. Beck 2023. 824 S. - Jürgen Kaube, Hegels Welt. Berlin: Rowohlt 2020. 592 S. Slavoj Žižek, Hegel im verdrahteten Gehirn. Frankfurt am Main: S. Fischer 2020. 288 S. - Yuval Noah Harari, 21 Lektionen für das 21. Jahrhundert. München: C.H. Beck 2019. 528 S. - Alexander Schubert, Phänomenologie des Zeitgeistes: Mit Hegel durchs 21. Jahrhundert. Wien: Passagen 2022. 136 S. - Catrin Misselhorn, Künstliche Intelligenz - das Ende der Kunst? Ditzingen: Reclam 2023. 152 S.